Service Quality Gap Analysis of Early Childhood Education at Ban Tera School, Pattani, Thailand - Nuradi, Anisa; Rosdiana, Rosdiana; Hasis, Pertiwi Kamariah (Universitas Negeri Makassar, 2025)
This study examines the quality of early childhood education services at Ban Tera School, Pattani, Thailand, using a gap analysis approach on five SERVQUAL dimensions: tangibility, reliability, responsiveness, assurance, and empathy. This research was motivated by the important role of early childhood education in child development, as well as the need to improve service quality in a socio-culturally dynamic region such as Pattani. This study aims to analyze: 1) the quality of early childhood education services at Ban Tera School Pattani Thailand, 2) the gap between parents’ perceptions and expectations of the quality of education services, and 3) service indicators that are considered important by parents according to the five dimensions of Service Quality (SERVQUAL). This type of research is quantitative research using the SERVQUAL analysis method. Data collection was carried out through distributing questionnaires to 30 respondents who were parents of children in early childhood. The questionnaire aims to measure service quality based on five main dimensions, namely tangibility, reliability, responsiveness, assurance, and empathy. The results showed that: 1) the overall quality of early childhood education services at Ban Tera School still has a gap between parents’ expectations and perceptions, with all dimensions showing negative gap values but still in the good category, 2) the largest to smallest gaps are the assurance dimension (-0.69), reliability (-0.59), empathy (-0.48), responsiveness (-0.43), and physical evidence (-0.35), and 3) Service indicators that are considered most important by parents are aspects that ensure safety and direct attention to child development, as well as the quality of the physical environment that supports children’s learning.